PENILAIAN AUTENTIK PADA MATAPELAJARAN PENDIDIKAN AGAMA ISLAM - Mohamad Aso Samsudin; Ukhtul Iffah (Fakultas Tarbiyah, Universitas Ibrahimy, 2019)
Teaching is an art means that the art of managing people who have a variety of different characters. The teacher should be able to recognize these different characters so that he can easily master them so that the subject is easily mastered by them. However, the teacher is not easy to do that. It is no less difficult in learning to do assessment, because when assessment teachers are required to be careful and meticulous so that the results are not wrong, be careful in determining appropriate measurement tools as measured, or careful in operating the right tools, especially teachers are required able to do a complete assessment (authentic) in three domains (cognitive, psychomotor, and affective). This article reviews how to carry out authentic assessments in Islamic Education (Pendidikan Agama Islam) learning.